Feasibility Study of the Time Reversal Symmetry Tests in Decay of Metastable Positronium Atoms with the J-PET Detector. (12th December 2018) - Gajos, A.; Curceanu, C.; Czerwiński, E.; Dulski, K.; Gorgol, M.; Gupta-Sharma, N.; Hiesmayr, B. C.; Jasińska, B.; Kacprzak, K.; Kapłon, Ł.; Kisielewska, D.; Korcyl, G.; et al.
Abstract : This article reports on the feasibility of testing of the symmetry under reversal in time in a purely leptonic system constituted by positronium atoms using the J-PET detector. The present state of T symmetry tests is discussed with an emphasis on the scarcely explored sector of leptonic systems. Two possible strategies of searching for manifestations of T violation in nonvanishing angular correlations of final state observables in the decay of metastable triplet states of positronium available with J-PET are proposed and discussed. Results of a pilot measurement with J-PET and assessment of its performance in reconstruction of three-photon decays are shown along with an analysis of its impact on the sensitivity of the detector for the determination of T -violation sensitive observables.